(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
The article analyzes the issues of individualization of the educational process within the framework of the Concept of Development of the Higher Education System of the Republic of Uzbekistan until 2030. The interrelation of external and internal individualization mechanisms in the formation of an educational environment that meets the personal characteristics, needs and interests of students is substantiated. Individualization as a pedagogical process is carried out through the personal activity, reflection and organization of independent educational activities of the student, as well as through methodological and technological means used by the teacher. The issues of forming individual educational trajectories, taking into account the student’s labor costs and increasing educational efficiency are revealed on the example of the credit-module system and the principles of ESTS. The results of the study indicate the need to strengthen the person-centered approach in higher education, expand students’ opportunities for self-awareness and independent determination of their educational path.